Green Synthesis of Nanolevel Polyoxometalate of Vanadium with Sulphur as Heteroatom - Hari Prasad, S.; Sreedhar, M.K.; Samuel, Jadu (Asian Journal of Chemistry, 2012)
Novel sulphovanadate nanospheres were prepared in a reaction of vanadium(V) oxide and an organic cationic surfactant dodecylpyridinium chloride (DPC) as structure directing template at the pH value of 3.0 under ordinary conditions of temperature and pressure by applying the principles of green chemistry. The specimen was characterized by Fourier transform infrared spectrascopy (FT-IR), which shows that the nano material consists of S-O, V-O, V=O and S-O-V linkages. Thermogravimetric analysis (TGA) shows that polyoxometalate contributes 60 % by weight of the sample. The X-ray diffraction analysis (XRD) shows that the particles are amorphous in nature. The high resolution transmission electron microscopic (HRTEM) analysis shows that the particles are the aggregation of particles of diameter below 10 nm. The nano scale dimension was further verified by atomic force microscopy.